BIM-Controlled Signage System for Building Evacuation. (2015) - Yenumula, K.; Kolmer, C.; Pan, J.; Su, X.
Abstract: Signage system is important to lead occupants to circulate as well as to evacuate people in emergency. Multiple exit signs leading to different directions at an intersection for general circulation may create confusion in people under emergency, and therefore can jeopardize the situation into a chaotic state, especially in buildings with a complex layout. Many past studies focused on implementing different techniques or designs to improve the existing signage system for better visual and navigating effects, such as the use of laser beams, the combination of audio and video cues, and the selection of color, location, and mounting height. How to better control the signage system under emergency has been overlooked. This paper proposed a BIM-controlled signage system to solve the problem. With the help of heat sensors that detect the fire prone areas in the building, the proposed system identifies the best route and activates the corresponding sign blinkers with high intensity. During this action, exit signs that do not lead to the best route become inactive. This system provides a natural interface for remote operation in facility management to efficiently guide people to the right exit under emergency. A prototype of the signage system is presented and future research directions are discussed.